Scatology as non-invasive tool for conservation of cheetah (Acinonyx jubatus Von Schreber, 1775) in South Africa - Van Van Marle-Koster, Este (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2010.